Probing the Links of LRMDS Implementation, Teacher Effectiveness, and Academic Gains in SOX Public Schools - Lamintao, Ivy; Cerado, Ernie (JPAIR, 2025)
This study assessed the interplay of carrying out the Department of Education’s Learning Resources Management and Development System (LRMDS) on teacher effectiveness and student academic gains in public junior high schools across the SOX Region. Anchored in Constructivist Learning Theory and the Theory of Planned Behavior, the study employed a descriptive-correlational research design, using structured surveys to collect data from teachers across the eight school divisions. A total of 307 teachers were randomly selected from 32 schools, representing four categories of schools in each division. Descriptive and inferential statistics were used to analyze the data. Results showed a high level of LRMDS implementation, primarily in the areas of accessibility, acceptability, and feedback mechanisms. Teachers exhibited a high degree of instructional effectiveness, characterized by the use of diverse pedagogical strategies and the design of dynamic learning environments. Students’ academic gain was consistently rated as very satisfactory across core subjects. Statistical analyses suggested a significant correlation between the level of LRMDS implementation and teacher effectiveness. Nonetheless, a significant but negative relationship was noted between LRMDS implementation and students’ academic gain. The study stresses the importance of enabling feedback mechanisms and increasing internet access to further boost the LRMDS’s role in promoting effective pedagogy and improved quality of outcomes in basic education.